Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.7727/wimj.2015.279
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variation by race in the male to female ratio at birth in the United States

Abstract: Objective: In humans, male exceed female live births. This ratio is conventionally referred to (M/F) male to female ratio and is used to denote male divided by total births. This ratio is influenced by a large number of factors and has been shown to exhibit seasonality. This study was carried out in order to ascertain whether seasonal variation in M/F exists in United States and whether such variations are influenced by race. Material and Methods: Births by gender and by race for 2003-13 were obtained from CDC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…Early studies had shown a low M/F in February and March and a high M/F in summer in various parts of the world (3) with similar patterns in the United States more recently (4).…”
Section: Introductionmentioning
confidence: 84%
“…Early studies had shown a low M/F in February and March and a high M/F in summer in various parts of the world (3) with similar patterns in the United States more recently (4).…”
Section: Introductionmentioning
confidence: 84%